Pengaruh Auditor Switching, Audit Tenure, Ukuran KAP, Solvabilitas, dan Opini Audit Terhadap Audit Report Lag - Putri, Widya Aprilya; Kusumawati, Eny (Paradoks : Jurnal Ilmu Ekonomi, 2025)
Audit report lag refers to the time taken by auditors to complete a company’s annual financial report. This study explores the impact of auditor switching, audit tenure, public accounting firm (KAP) size, solvency, and audit opinion on audit report lag in primary consumer goods companies listed on the Indonesia Stock Exchange from 2021 to 2023. Using purposive sampling, a total of 153 observations met the criteria for analysis. The data were analyzed through multiple linear regression, with all classical assumption tests satisfied. The findings reveal that auditor switching and the size of the audit firm significantly influence the length of the audit report lag. In contrast, audit tenure, solvency, and audit opinion show no significant effect. These insights are valuable for companies, investors, and regulators in encouraging timely submission of audited financial statements, which is essential for maintaining transparency, trust, and efficient decision-making in the capital market.